2008
DOI: 10.1021/la704078u
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Dot Self-Assembly for Protein Detection with Sub-Picomolar Sensitivity

Abstract: A novel approach to sensitive and rapid antigen detection is described. In the presence of a specific antigen, quantum dot-antibody conjugates rapidly self-assemble into agglomerates that are typically more than 1 order of magnitude larger than their individual components. The size distribution of the agglomerated colloids depends on, among other things, the relative concentration of quantum dot conjugates and antigen molecules. Quantum dot agglomerates mediated by antigen recognition were characterized by mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…In this scheme, QD-Ab conjugates rapidly aggregate in the presence of antigens, resulting in colloidal structures that are 1-2 orders of magnitude larger in size than the constituents [9]. These structures are detected by light scattering in a flow cytometer [9]. The detection of various antigens using QDs with different emission properties is possible with this straightforward agglomeration-based detection strategy.…”
Section: Quantum Dotsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this scheme, QD-Ab conjugates rapidly aggregate in the presence of antigens, resulting in colloidal structures that are 1-2 orders of magnitude larger in size than the constituents [9]. These structures are detected by light scattering in a flow cytometer [9]. The detection of various antigens using QDs with different emission properties is possible with this straightforward agglomeration-based detection strategy.…”
Section: Quantum Dotsmentioning
confidence: 99%
“…Since the interaction between CrAsH and cysteine causes a significant increase in CrAsH's fluorescence, nanohybrids of CrAsH-QD could serve as a probe to locate Cys-tagged proteins and subsequently trace them for more than 150 s, taking advantage of the high resistance of QDs to photobleaching [8]. On the other hand, Soman et al profited from the much larger size of QDs than organic dyes when designing a protein detection scheme that offers subpicomolar sensitivity [9]. In this scheme, QD-Ab conjugates rapidly aggregate in the presence of antigens, resulting in colloidal structures that are 1-2 orders of magnitude larger in size than the constituents [9].…”
Section: Quantum Dotsmentioning
confidence: 99%
See 1 more Smart Citation
“…4, the RLS intensity of QDs-rabbit anti-AIV H5N1 antibody was remarkably increased in the presence of H5N1 viral antigen, which showed that larger particles were formed based on the immunoreaction between H5N1 viral antigen and the QDs-rabbit anti-AIV H5N1 antibody probe. (19) Further evidence for the eff ect of QDs-rabbit anti-AIV H5N1 antibody probe was also confi rmed by FL imaging. Figure 5 showed two FL imagings from the sandwich conjugates bound on microplates after sFLISA.…”
Section: Characterization Of Cdte Qds and Qds-rabbit Anti-aiv H5n1 Anmentioning
confidence: 91%
“…Additional embodiments include the use of the same device to detect alternate biomarkers associated with response to therapy, which reduces patient exposure to ineffective therapies, minimize the development of ntion includes monitoring disease relapse following successful treatment in a sensitive and rapid way at the 'point-of-care', effectively addressing a critical concern shared by all cancer survivors [9].…”
Section: Nanoparticle and Nanowire For Proteomic Biomarker In Cancer mentioning
confidence: 99%